Vasopressin Promoter Transgenic and Vasopressin Gene-Edited Ascidian, Ciona intestinalis Type A (Ciona robusta): Innervation, Gene Expression Profiles, and Phenotypes - Kawada, Tsuyoshi; Shiraishi, Akira; Matsubara, Shin; Hozumi, Akiko; Horie, Takeo; Sasakura, Yasunori; Satake, Honoo (Frontiers in Endocrinology, 2021)
Oxytocin (OT) and vasopressin (VP) superfamily neuropeptides are distributed in not only vertebrates but also diverse invertebrates. However, no VPergic innervation of invertebrates has ever been documented. In the ascidian, Ciona intestinalis Type A (Ciona robusta), an OT/VP superfamily peptide was identified, and the Ciona vasopressin (CiVP) induces oocyte maturation and ovulation. In the present study, we characterize the innervation and phenotypes of genetically modified Ciona: CiVP promoter-Venus transgenic and CiVP mutants. CiVP promoter-Venus transgenic Ciona demonstrated that CiVP gene was highly expressed in the cerebral ganglion and several nerves. Fluorescence was also detected in the ovary of young CiVP promoter-Venus transgenic ascidians, suggesting that the CiVP gene is also expressed temporarily in the ovary of young ascidians. Furthermore, a marked decrease of post-vitellogenic (stage III) follicles was observed in the ovary of CiVP mutants, whereas pre-vitellogenic (stage I) and vitellogenic (stage II) follicles were increased in the mutant ovary, compared with that of wildtype Ciona. Gene expression profiles showed that the expression of various genes, including genes related to ovarian follicle growth, was altered in the ovary of CiVP mutants. Altogether, these results indicated that CiVP, mainly as a neuropeptide, plays pivotal roles in diverse biological functions, including growth of early-stage ovarian follicles via regulation of the expression of a wide variety of genes. This is the first report describing a VP gene promoter-transgenic and VP gene-edited invertebrate and also on its gene expression profiles and phenotypes.